GABA-Glycine Cotransmitting Neurons in the Ventrolateral Medulla: Development and Functional Relevance for Breathing - Hirrlinger, Johannes; Marx, Grit; Besser, Stefanie; Sicker, Marit; Köhler, Susanne; Hirrlinger, Petra G.; Wojcik, Sonja M.; Eulenburg, Volker; Winkler, Ulrike; Hülsmann, Swen (Frontiers in Cellular Neuroscience, 2019)
Inhibitory neurons crucially contribute to shaping the breathing rhythm in the brain stem. These neurons use GABA or glycine as neurotransmitter; or co-release GABA and glycine. However, the developmental relationship between GABAergic, glycinergic and cotransmitting neurons, and the functional relevance of cotransmitting neurons has remained enigmatic. Transgenic mice expressing fluorescent markers or the split-Cre system in inhibitory neurons were developed to track the three different interneuron phenotypes. During late embryonic development, the majority of inhibitory neurons in the ventrolateral medulla are cotransmitting cells, most of which differentiate into GABAergic and glycinergic neurons around birth and around postnatal day 4, respectively. Functional inactivation of cotransmitting neurons revealed an increase of the number of respiratory pauses, the cycle-by-cycle variability, and the overall variability of breathing. In summary, the majority of cotransmitting neurons differentiate into GABAergic or glycinergic neurons within the first two weeks after birth and these neurons contribute to fine-tuning of the breathing pattern.